Analysıs Of Refreezıng Change Model On Performance Of Kenya Broadcastıng Corporatıon - Vivian Isiche; Evans Nyamboga Mandere (Cita Konsultindo Research Center, 2024)
The Kenya Broadcasting Corporation (KBC), like many organizations, faces the challenge of adapting to a dynamic environment. To enhance its performance, KBC has implemented various strategies, including sustainable programs. However, intense competition from other licensed stations, such as Citizen TV, KTN News, KTN Home, NTV, K24, and TV47, has impacted KBC’s performance. Over the years, KBC has transitioned from being a top media house to a struggling station. This study investigated the influence of refreezing Change Management Model on KBC’s performance. Refreezing change is one of the components of Lewin’s model, which comprises three stages; - Unfreeze, Change, and Refreeze and provides a structured approach to managing organizational change. The study was informed on the basis of Kurt Lewin change management model, Mckinsey 7s model, ADKAR change management model, Kotter’s Eight -step change model, kubler-Rose change curve and Nudge theory, thus proving a comprehensive framework for change managment. A descriptive research strategy was used for this investigation. One hundred and thirty-two employees of the Organization made up the sample population. Sampling was performed using the census technique. Primary data collection involved self-administration of questionnaires. Presentation was done using tables, figures and charts.The overall implication of the study shows that refreezing is currently being used by KBC to improve improving KBC’s operational efficiency and effectiveness and hence performance. Major conclusion is that the departmental heads at KBC (Kenya Broadcasting Corporation) generally agree that the process of “refreezing” (disrupting existing routines and mindsets) has a positive impact on KBC’s performance to a great extent. The study offers actionable recommendations such as: KBC should invest in training programs and effective communication strategies to ensure that employees understand and embrace the refreezing process; regular monitoring of the impact of refreezing initiatives on performance metrics and adjusts strategies accordingly ensuring alignment between departmental heads and KBC leaders in communicating the importance of unfreezing. The study contributes to the body of knowledge by offering empirical and practical evidence of refreezing stage of Lewin’s Change Management Model and its significance in organizational performance.